Listening to Music Through Participation: Effects on Musical Understanding and on the Argumentative Competence in Spontaneous Judgements - Godinho, José Carlos (2018)
This paper focuses on listening to music through participation, which refers to the act of listening to recorded music with simultaneous participation of the listeners. The strategies that will be analysed include instrumental percussion and miming activities during the act of listening to classical music. Previous studies have compared these strategies with the situation of listening in silence and have pointed to some positive effects that listening through participation promotes both on musical memory and on the organization of mental representation. Those studies were conducted with aural and visual identification tests, without involving written or spoken language. This new study focuses on the analysis of musical descriptions, written by children in different listening contexts. The results point to some positive effects that instrumental percussion and miming activities have on musical understanding and judgment, in comparison with the strategy of listening in silence.